RECENT ADVANCES IN NANOCARRIER BASED THERAPEUTIC AND DIAGNOSTIC TOOLS FOR COLORECTAL CANCER - Shaji, Jessy; Menon, Ipshita (International Journal of Current Pharmaceutical Research, 2015)
Colorectal cancer (CRC) is among the frequently diagnosed cancers and one of the leading causes of deaths in the world. It has remarkably high rates of metastasis, which incidentally is one of the leading causes of CRC related deaths. Ineffective drug concentration at the desired site of action and toxicity due to peripheral targeting limits the efficacy of the conventional chemotherapeutic treatments. Currently used traditional diagnostic tools have various shortcomings such as poor intracellular contrast between malignant and benign cells and low detection sensitivity in biological environment. Smarter drug delivery systems based on nano carriers have been proven remarkably promising in enhancing drug distribution and bioavailability, increasing half-life and achieving targeted drug delivery, thus, minimizing toxicity. Diagnosis employing nanoparticles is more effective in terms of stability, duration and efficiency. CRC targeting, both for drug delivery as well as diagnosis, is improved manifold by incorporating ligands of tumor specific surface receptors on the nanoparticles. Recently documented data have furnished cogent evidence apropos, the potential of active-targeted nanotherapeutics, and diagnostics in CRC therapy involving myriad forms of nanoparticles. This review deliberates the current status of nanocarriers, and the significance of their use in colorectal cancer therapy.